The Ties That Bind: Social Capital, Families, and Children's Well‐Being. (25th December 2015) - Parcel, Toby L.; Bixby, Monica S.
Abstract: Social bonds between parents and their children, an important form of social capital, promote children's cognition and their social adjustment. Both bonding and bridging social capital are consequential, as are parental norms and values, which vary by social class. Parents' working conditions, including occupational complexity and work schedules, influence children's home environments as well as their children's development. Family social capital is more important than school social capital in influencing both cognitive and social child outcomes. Recent studies show how fathers' roles are changing, with implications for social capital in families, and point to bonding with fathers as a possible mechanism for building social capital. We know relatively little about how different forms of capital, including financial, human, cultural, and social capital, combine to influence families and children. We need further analyses regarding how to build social capital, particularly for at‐risk children.